Synalpheus amintae sp. nov., a new species of sponge–dwelling snapping shrimp (Crustacea: Decapoda: Alpheidae) from Parque Nacional Natural Isla Gorgona, Pacific Coast of Colombia - Ramos-Tafur, Gabriel E.; Franke-Ante, Rebeca (Zootaxa, 2019)
A new species of sponge–dwelling snapping shrimp, Synalpheus amintae sp. nov. from the Parque Nacional Natural Isla Gorgona, Pacific coast of Colombia, is described. This new species pertains to the denominated Synalpheus “Gambarelloides” species group sensu Coutière (1909)—previously known as “Laevimanus” group. It was collected in the southern part of the Island, during episodes of extreme low tides, known locally as “puja”. Synalpheus amintae sp. nov. is closely related to the only two other known species of the S. “Gambarelloides” species group from the eastern Pacific: Synalpheus occidentalis Coutière, 1909, from Gulf of San José, Lower California, and Synalpheus mulegensis Ríos, 1992, from Bahía Concepción, Gulf of California, and can be differentiated from them by the poorly developed distal portion of pollex of the major cheliped, the armature of the distal segment of third maxilliped, and the number of acute teeth of exopodal uropod. A discriminative analysis dealing with other three species of Synalpheus from the western Atlantic, with distinctive pollex of major chela reduced, is presented. A dichotomous key was elaborated to identify the species of Synalpheus “Gambarelloides” species group from the eastern Pacific. The number of valid species described of Synalpheus from the eastern Pacific is increased to 23.